BARICITINIB IN THE BASIC THERAPY OF RESISTANT RHEUMATOID ARTHRITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The review presents the latest data on the use of the selective Janus kinase inhibitor (jak) baricitinib (BARI) in patients with rheumatoid arthritis (RA). The results of the use of BARI in RA indicate that it is comparable in effectiveness to genetically engineered biological drugs (GIBP) and tofacitinib, while showing the possibility of achieving the goal of therapy to reduce the dose of BARI to 2 mg / day without loss of effect in most patients and relief of exacerbation that occurred against the background of a reduced dose. According to data from registries in many countries and open observational studies, BARI has good tolerance for long-term use, including in older patients with ≥1 risk factor for cardiovascular diseases. There was also a high survival rate of BARI therapy, exceeding, according to some registries, that of tumor necrosis factor α inhibitors. Against the background of taking BARI, rapid (within 1-3 months) a statistically significant reduction in pain, regardless of the degree of suppression of disease activity, correlated with an improvement in the functional status and general condition of patients. The possibility of suppressing the progression of structural damage in RA patients has also been shown, which makes it possible to choose an individual management strategy for such patients.